Kalvak, Ca. 1902-1983 - Bushman, Leo (ARCTIC, 1984)
Anyone who has seen the Holman Island Inuit printmakers' work, on calendars, in museums, or in galleries, will recognize the unique style of Kalvak. She did not begin drawing until she was in her late fifties or early sixties, and it is fortunate for her admirers that Father Henry Tardy had the foresight to save many of Kalvak's early drawings. . I counted over 900 pencil and marking-pen drawings by Kalvak in the early 1970s, many of which were later translated into prints. Kalvak's subjects were a mixture of her physical environment, animals, and shamanism; her vision captured the true nature of the far north. That vision will live on to enrich our enjoyment and understanding. Kalvak was awarded the Order of Canada in 1979. A film released in 1970 by the University of Calgary Communications Department shows many of her drawings as well as Kalvak herself in her prime.